2019
DOI: 10.4103/njms.njms_25_18
|View full text |Cite
|
Sign up to set email alerts
|

A rare nonsyndromic case of adenomatoid odontogenic tumor associated with multiple impacted supernumerary teeth

Abstract: Adenomatoid odontogenic tumour (AOT) is a rare benign odontogenic tumour characterized by a progressively slow growing pattern and symptomless behavior. The differential diagnosis between AOT and other odontogenic tumours, such as ameloblastoma, should be well conducted in order to avoid extensive ablative surgery. The present case report is of a 27 year old female who reported with a chief complaint of mild intermittent pain and a swelling which was gradually increasing in size, on the left mid-facial region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…The most prevalent anomaly found was supernumerary teeth (4.25%); other frequently found anomalies were paramolars and mesiodens. These findings are in keeping with the results of other studies by Ooshima et al in Japan and Mohanty et al in the United States [9,19]. Research by Hamasha et al who carried out similar epidemiological studies, revealed that certain anomalies like microdontia and talons cusp showed the least prevalence among all other anomalies [20].…”
Section: Discussionsupporting
confidence: 90%
“…The most prevalent anomaly found was supernumerary teeth (4.25%); other frequently found anomalies were paramolars and mesiodens. These findings are in keeping with the results of other studies by Ooshima et al in Japan and Mohanty et al in the United States [9,19]. Research by Hamasha et al who carried out similar epidemiological studies, revealed that certain anomalies like microdontia and talons cusp showed the least prevalence among all other anomalies [20].…”
Section: Discussionsupporting
confidence: 90%
“…Kundoor et al 6 mentions it also presents tubular or ductiform structures surround by a central space delimited by a layer of columnar or cubic epithelial cells with cells demonstrating polarized nucleus 10,13,23 . Small foci of calcification may also be observed 24 . In this report, the histopathological examination is similar with the characteristics described above.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Malignant tumors must be ruled out because dentigerous cysts can develop into other tumor types, including squamous cell carcinoma and mucoepidermoid carcinoma. 11 , 13 A rare case of an adenomatoid odontogenic tumor associated with impacted supernumerary teeth was reported by Mohanty et al 11 It is difficult to diagnose a dentigerous cyst at the initial visit. Therefore, a histopathological examination is necessary to reach a definitive diagnosis because the clinical diagnosis may be confused with another type of odontogenic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of dentigerous cysts includes ameloblastoma, odontogenic keratocyst, odontogenic fibroma, radicular cyst, residual cyst, odontogenic myxoma, adenomatoid odontogenic tumor, odontoma, and Pindborg tumor, [9][10][11][12][13][14] all of which may have a similar radiographic appearance. Occasionally, a dentigerous cyst must be differentiated from a retention cyst of the maxillary sinus mucosa when maxillary sinus mucosa hypertrophy is involved.…”
Section: Discussionmentioning
confidence: 99%